Pengaruh Literasi Wakaf, Advertensi dan Religiusitas terhadap Minat Masyarakat Kota Makassar untuk Berwakaf Uang dengan Transparansi sebagai Variabel Moderating - Firawati, Firawati; Katman, Muhammad Nasir; masse, Rahman Ambo (ANWARUL, 2024)
The aim of this research is to examine the extent to which waqf literacy, advertising and religiosity have an impact on the interest of the people of Makassar City to give cash waqf. This research uses a quantitative descriptive research design. This research relies on primary and secondary data sources. In this research, questionnaires, interviews and documentation were used to collect data. The SmartPLS 4.0 data processing application is used in research data analysis. Based on the regression results, the variables Literacy (X1), Advertising (X2), and Religiosity (X3) have a positive and large influence on the variable Interest in donating cash (Y). Furthermore, the variable Transparency (Z) cannot moderate (weaken) the influence of waqf literacy and cannot moderate (weaken) the influence of religiosity but can moderate (strengthen) the influence of advertising on people's interest in cash waqf.